Steroid dimers : chemistry and applications in drug design and delivery - Nahar, Lutfun, Ph. D.; Sarker, Satyajit D. (Chichester, West Sussex, UK : John Wiley & Sons, 2012)
Steroid dimers are an important group of compounds produced by various marine organisms, and also synthesized in the laboratories. This group of compounds possesses various pharmacological and biological properties, and can also be used to create€ & ldquo;molecular umbrellas & rdquo; for drug delivery. Steroid Dimers: Chemistry and Applications in Drug Design and Delivery provides an up-to-date overview on the chemistry and applications of steroid dimers of natural and synthetic origins. The book includes easy-to-follow synthetic protocols for various classes of important dimeric steroids.
Introduction -- Synthesis of acyclic steroid dimers -- Synthesis of cyclic steroid dimers -- Naturally occurring steroid dimers -- Synthesis of cephalostatin and ritterazine analogues -- Applications of steroid dimers.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Steroids; Dimers; Drug delivery systems; Drugs -- Design; Steroids -- chemistry; Dimerization; Drug Delivery Systems; Drug Design; SCIENCE -- Life Sciences -- Biochemistry; Dimers; Drug delivery systems; Drugs -- Design; Steroids; Electronic books